A preliminary study on the effects of wildfire on some physical and chemical properties of clayey soil in Gandafora AL-Jabal alkhdar – Libya - أمين فوزي محمد الدومي; أدريس المبروك أبوبكر حمد; صفوت ميكائيل عمر (African Journal of Advanced Pure and Applied Sciences, 2025)
This preliminary field study was conducted to investigate the possible effects of wildfire on some physical and chemical properties of soil of Gandafora in Jabal Al-Akhdar east of Libya. Two sites having similar environmental and topographic features were selected. One site had been exposed to the effects of wildfire about two decades ago while the other site has not been affected by wildfire and remained under the prevailing environmental conditions of the area. To achieve the objectives of this field study representative composite soil samples were collected at depths 0-20, 20-40 cm. Soil properties sensitive to the effects of wildfire as reported in several research papers were investigated. The traits included were field moisture content, texture, structure, porosity and infiltration rate. Also, soil reaction (pH), electric conductivity(EC) and the percentage of soil organic matter (OM) content. The data collected were subjected to statistical analyses (ANOVA) which indicated no significant difference between the two sites at 0.05 level of significance in texture, field moisture content, pH and EC. However, significant differences were found between OM content of soils representing these two sites. Additionally, the data have confirmed an important increase of surface soil BD exposed to wildfire leading to higher surface compaction, less porosity and lower infiltration rate.